Artificial stone composition, preparation method thereof and application thereof

By adopting artificial stone compositions, composed of silicate fillers, resins and stabilizers, and preparing through vacuum compression and heating curing processes, the problems of poor stability and resource consumption of existing engineering stone products are solved, and high-performance and environmentally friendly building materials are achieved.

CN117303798BActive Publication Date: 2025-04-04FUJIAN ULTRACERA NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311255345.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-04
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

Existing engineered stone products have poor stability when affected by factors such as light, temperature, water, bacteria, etc., and are prone to dust and noise pollution during their preparation, and quartz sand resources are gradually consumed.

Method used

An artificial stone composition is used, which consists of a silicate filler, a resin, a stabilizer, a colorant, an initiator and a coupling agent, and is prepared by a vacuum compression and heating curing process. It is preferred that aluminosilicate and sodium magnesium silicate are used as silicate fillers. The glass transition temperature of the resin is not less than 80°C. The stabilizer consists of an antibacterial agent, a hydrophobic agent, a nanomaterial or a fiber material.

Benefits of technology

It significantly improves the mechanical properties of the artificial stone composition, has good resistance to temperature difference damage, water swelling and cracking resistance, weather resistance and bacteria resistance, reduces the generation of aging waste, reduces the cost of materials and construction costs, and has the advantages of greening and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117303798B_ABST
    Figure CN117303798B_ABST
Patent Text Reader

Abstract

The present invention relates to an artificial stone composition, which contains 80-95% silicate filler, 4-15% resin, 0.1-5% stabilizer, 0.05-5% colorant, 0.05-5% initiator and 0.05-5% coupling agent in weight percentage, wherein the silicate is selected from any one or a combination of aluminum silicate and sodium magnesium silicate, the silicate filler particle size is 6 mesh-1000 mesh, the glass transition temperature of the resin is not less than 80°C, and the stabilizer is composed of any one or a combination of antibacterial agent: hydrophobic agent: nano material or fiber material according to a mass ratio of 1:1-10:3-20. The artificial stone composition of the present invention has good resistance to temperature difference destructiveness, water cracking resistance, weather resistance and bacteria resistance, effectively avoids the generation of aging waste, significantly reduces the material cost and the construction cost of replacing materials, and has the advantages of greening and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to an artificial stone composition, a preparation method thereof and applications thereof. Background Art

[0002] Engineered stone products are mostly made of quartz as the main component, and have advantages over natural stone products such as low porosity, good durability and similar aesthetic characteristics. They are widely used in the preparation of countertops, floors, furniture surfaces, architectural decorative panels, wall tiles, etc. However, engineered stone products have the following defects: First, their stability is affected by factors such as light, temperature, water, and bacteria, including yellowing due to ultraviolet radiation, breaking due to temperature differences, expansion and cracking of the board due to water penetration or accumulation, and corrosion and damage of the board caused by bacteria; second, the preparation of quartz stone boards is prone to dust pollution and noise pollution, which affects the health of operators and increases environmental governance costs; third, the use of quartz sand is limited by the reality that quartz sand resources are gradually being consumed. For this reason, it is urgent to develop an artificial stone board with good stability to meet market demand. Summary of the invention

[0003] The object of the present invention is to provide an artificial stone composition, which contains, by weight percentage, 80-95% of silicate filler, 4-15% of resin, 0.1-5% of stabilizer, 0.05-5% of colorant, 0.05-5% of initiator and 0.05-5% of coupling agent, wherein the silicate is selected from any one of aluminum silicate and sodium magnesium silicate or a combination thereof, the particle size of the silicate filler is 6 mesh to 1000 mesh, the glass transition temperature of the resin is not less than 80°C, and the stabilizer is composed of an antibacterial agent: a hydrophobic agent: a nano material or a fiber material in a mass ratio of 1:1-10:3-20.

[0004] In the preferred technical solution of the present invention, the aluminum element: silicon element: oxygen element in the aluminosilicate is composed according to a mass ratio of 1:1-10:1-10, and preferably the aluminum element: silicon element: oxygen element in the aluminosilicate is composed according to a mass ratio of 1:(1.5-5):(3-8).

[0005] In the preferred technical solution of the present invention, the mass ratio of magnesium element: sodium element: silicon element: oxygen element in the sodium magnesium silicate is 1:1-10:10-20:20-30, and preferably the mass ratio of magnesium element: sodium element: silicon element: oxygen element in the sodium magnesium silicate is 1:(5-8):(10-15);(25-30).

[0006] In a preferred technical solution of the present invention, the glass transition temperature of the resin is not less than 100°C.

[0007] In a preferred technical solution of the present invention, the stabilizer is composed of an antibacterial agent: a hydrophobic agent: a nano material or a fiber material in a mass ratio of 1:1-2:5-10.

[0008] In the preferred technical solution of the present invention, the mass ratio of aluminum silicate to sodium magnesium silicate in the composition is 1-5:1, preferably 1-3:1, in weight percentage.

[0009] In a preferred technical solution of the present invention, the quartz sand contained in the composition is ≤4% by weight, preferably ≤3%, more preferably ≤2%, and further preferably ≤1%.

[0010] In a preferred technical solution of the present invention, the composition substantially does not contain quartz sand.

[0011] The term "substantially free of quartz sand" in the present invention means that quartz sand is not detected in the composition or the quartz sand contained in the composition is zero.

[0012] In the preferred technical solution of the present invention, the composition contains 10-15% of resin by weight.

[0013] In a preferred technical solution of the present invention, the resin is selected from resins without benzene rings and / or conjugated double bonds, preferably any one of petroleum resins, alkyd resins, acrylic resins, unsaturated polyester resins, polyether resins, polyester resins, or a combination thereof.

[0014] In the preferred technical solution of the present invention, the resin is ORCHEM TM Any one of 727 unsaturated polyester resin, SIL93BE-956 resin, Brayton type polyester resin or a combination thereof.

[0015] In the preferred technical solution of the present invention, the composition contains 0.3-3% of stabilizer by weight.

[0016] In a preferred technical solution of the present invention, the nano material is selected from any one of nano oxides, nano carbides, nano borides, and nano nitrides, or a combination thereof.

[0017] In a preferred technical solution of the present invention, the particle size of the nanomaterial is not higher than 500 nm.

[0018] In a preferred technical solution of the present invention, the fiber material is selected from any one of carbon fiber, glass fiber, aramid fiber or a combination thereof.

[0019] In a preferred technical solution of the present invention, the length of the fiber material is not less than 3 mm.

[0020] In the preferred technical scheme of the present invention, the antibacterial agent is selected from any one of alcohol antibacterial agents, silver antibacterial agents, imidazole antibacterial agents, copper antibacterial agents, zinc antibacterial agents, aldehyde antibacterial agents, acylanilide antibacterial agents, thiazole antibacterial agents, ketone antibacterial agents, biguanide antibacterial agents, and phenolic antibacterial agents or a combination thereof.

[0021] In the preferred technical solution of the present invention, the antibacterial agent is selected from any one of phenoxyethanol (PHE-SP10), Germall IS45, and ZEOMIC AWION, or a combination thereof.

[0022] In a preferred technical solution of the present invention, the hydrophobic agent is selected from any one of an organosilicon hydrophobic agent, paraffin, a fluorocarbon polymer hydrophobic agent, and a fatty acid soap, or a combination thereof.

[0023] In a preferred technical solution of the present invention, the hydrophobic agent is selected from any one of Wacker BS4004, TEGO Phobe 1500N, paraffin, or a combination thereof.

[0024] In the preferred technical solution of the present invention, the composition contains 0.05-1% of the colorant by weight.

[0025] In the preferred technical solution of the present invention, the colorant is selected from any one or a combination of iron oxide colorants, titanium oxide colorants, phthalocyanine colorants, azo colorants, and methylcalcein complexes, and is preferably selected from any one or a combination of titanium dioxide, phthalocyanine blue, and iron oxide red.

[0026] In the preferred technical solution of the present invention, the composition contains 0.05-1% of the initiator by weight.

[0027] In a preferred technical solution of the present invention, the initiator is selected from any one of an azo initiator and a peroxide initiator or a combination thereof.

[0028] In the preferred technical solution of the present invention, the composition contains 0.05-1% of the coupling agent by weight.

[0029] In a preferred technical solution of the present invention, the coupling agent is selected from any one of a silane coupling agent, a titanate coupling agent, and an aluminate compound, or a combination thereof.

[0030] In a preferred technical solution of the present invention, the artificial stone composition does not contain cobalt element.

[0031] In the preferred technical solution of the present invention, the composition contains, by weight percentage, 80-90% aluminosilicate, 8-15% resin, 0.1-5% stabilizer, 0.05-1% colorant, 0.05-1% initiator and 0.05-1% coupling agent.

[0032] In the preferred technical solution of the present invention, the composition contains, by weight percentage, 40-65% of aluminum silicate, 25-45% of sodium magnesium silicate, 8-15% of resin, 0.1-5% of stabilizer, 0.05-1% of colorant, 0.05-1% of initiator and 0.05-1% of coupling agent.

[0033] In the preferred technical solution of the present invention, the composition contains 87.38% aluminosilicate, ORCHEM TM 727 unsaturated polyester resin 11.64%, titanium dioxide 0.29%, silane coupling agent (KH-570) 0.1%, azobisisobutyronitrile 0.1%, Germall IS45 0.1%, TEGO Phobe 1500N 0.1% and nano-alumina 0.29%.

[0034] In the preferred technical scheme of the present invention, the composition contains, by weight percentage, 60.52% of aluminum silicate, 27.93% of sodium magnesium silicate, 10.24% of SIL93BE-956 resin, 0.09% of phthalocyanine blue, 0.09% of silane coupling agent (KH-570), 0.09% of azobisisobutyronitrile, 0.1% of ZEOMIC AW10N, 0.2% of paraffin and 0.74% of glass fiber.

[0035] In the preferred technical solution of the present invention, the composition contains, by weight percentage, 46.17% aluminum silicate, 41.55% sodium magnesium silicate, 11.08% Brayton polyester resin, 0.09 parts of red iron oxide, 0.09% silane coupling agent (KH-570), 0.09% azobisisobutyronitrile, 0.09% PHE-SP10, 0.1% Wacker BS4004, and 0.74% carbon fiber.

[0036] In a preferred technical solution of the present invention, the UV resistance test of the artificial stone composition is above level 5, preferably above level 6.

[0037] In a preferred technical solution of the present invention, the artificial stone composition does not turn yellow when placed outdoors for more than 2 years, preferably for more than 5 years.

[0038] In a preferred technical solution of the present invention, the artificial stone composition does not crack when placed outdoors for more than 2 years, preferably for more than 5 years.

[0039] In a preferred technical solution of the present invention, the preparation of the artificial stone composition comprises the following steps:

[0040] (1) Weighing required amounts of stabilizer, colorant, coupling agent, and initiator, adding them to required amounts of resin, stirring until the mixture is uniform, and then sequentially adding a 100-1000 mesh silicate filler and a 6-100 mesh silicate filler under stirring to prepare a mixture;

[0041] (2) Under a vacuum degree of -0.1 MPa, the obtained mixture is vacuum-compressed to obtain a sheet precursor;

[0042] (3) The prepared board precursor is heated and solidified to obtain a board product.

[0043] In the preferred technical solution of the present invention, the stirring conditions in step (1) are 100-300 r / min*1-30 min, preferably 150-250 r / min*5-25 min.

[0044] In a preferred technical solution of the present invention, the compression in step (2) is vibration compression for 1-60 minutes.

[0045] In the preferred technical solution of the present invention, the curing conditions in step (3) are 70°C-150°C*10-300min, preferably 85°C-110°C*20-200min, and more preferably 90-100°C*30-100min.

[0046] Another object of the present invention is to provide a method for preparing an artificial stone composition, wherein the artificial stone composition contains, by weight percentage, 80-95% of a silicate filler, 4-15% of a resin, 0.1-5% of a stabilizer, 0.05-5% of a colorant, 0.05-5% of an initiator, and 0.05-5% of a coupling agent, wherein the silicate is selected from any one of aluminum silicate and sodium magnesium silicate or a combination thereof, the particle size of the silicate filler is 6 mesh to 1000 mesh, the glass transition temperature of the resin is not less than 80° C., the stabilizer is composed of an antibacterial agent: a hydrophobic agent: a nano material or a fiber material in a mass ratio of 1:1-10:3-20, and the preparation of the artificial stone composition comprises the following steps:

[0047] (1) Weighing required amounts of stabilizer, colorant, coupling agent, and initiator, adding them to required amounts of resin, stirring until the mixture is uniform, and then sequentially adding a 100-1000 mesh silicate filler and a 6-100 mesh silicate filler under stirring to prepare a mixture;

[0048] (2) Under a vacuum degree of -0.1 MPa, the obtained mixture is vacuum-compressed to obtain a sheet precursor;

[0049] (3) The prepared board precursor is heated and solidified to obtain a board product.

[0050] In the preferred technical solution of the present invention, the stirring conditions in step (1) are 100-300 r / min*1-30 min, preferably 150-250 r / min*5-25 min.

[0051] In a preferred technical solution of the present invention, the compression in step (2) is vibration compression for 1-60 minutes.

[0052] In the preferred technical solution of the present invention, the curing conditions in step (3) are 70°C-150°C*10-300min, preferably 85°C-110°C*20-200min, and more preferably 90-100°C*30-100min.

[0053] In the preferred technical solution of the present invention, the aluminum element: silicon element: oxygen element in the aluminosilicate is composed according to a mass ratio of 1:1-10:1-10, and preferably the aluminum element: silicon element: oxygen element in the aluminosilicate is composed according to a mass ratio of 1:(1.5-5):(3-8).

[0054] In the preferred technical solution of the present invention, the mass ratio of magnesium element: sodium element: silicon element: oxygen element in the sodium magnesium silicate is 1:1-10:10-20:20-30, and preferably the mass ratio of magnesium element: sodium element: silicon element: oxygen element in the sodium magnesium silicate is 1:(5-8):(10-15);(25-30).

[0055] In a preferred technical solution of the present invention, the glass transition temperature of the resin is not less than 100°C.

[0056] In a preferred technical solution of the present invention, the stabilizer is composed of an antibacterial agent: a hydrophobic agent: a nano material or a fiber material in a mass ratio of 1:1-2:5-10.

[0057] In the preferred technical solution of the present invention, the mass ratio of aluminum silicate to sodium magnesium silicate in the composition is 1-5:1, preferably 1-3:1, in weight percentage.

[0058] In a preferred technical solution of the present invention, the quartz sand contained in the composition is ≤4% by weight, preferably ≤3%, more preferably ≤2%, and further preferably ≤1%.

[0059] In a preferred technical solution of the present invention, the composition substantially does not contain quartz sand.

[0060] The term "substantially free of quartz sand" in the present invention means that quartz sand is not detected in the composition or the quartz sand contained in the composition is zero.

[0061] In the preferred technical solution of the present invention, the composition contains 10-15% of resin by weight.

[0062] In a preferred technical solution of the present invention, the resin is selected from resins without benzene rings and / or conjugated double bonds, preferably any one of petroleum resins, alkyd resins, acrylic resins, unsaturated polyester resins, polyether resins, polyester resins, or a combination thereof.

[0063] In the preferred technical solution of the present invention, the resin is ORCHEM TM Any one of 727 unsaturated polyester resin, SIL93BE-956 resin, Brayton type polyester resin or a combination thereof.

[0064] In the preferred technical solution of the present invention, the composition contains 0.3-3% of stabilizer by weight.

[0065] In a preferred technical solution of the present invention, the nano material is selected from any one of nano oxides, nano carbides, nano borides, and nano nitrides, or a combination thereof.

[0066] In a preferred technical solution of the present invention, the particle size of the nanomaterial is not higher than 500 nm.

[0067] In a preferred technical solution of the present invention, the fiber material is selected from any one of carbon fiber, glass fiber, aramid fiber or a combination thereof.

[0068] In a preferred technical solution of the present invention, the length of the fiber material is not less than 3 mm.

[0069] In the preferred technical scheme of the present invention, the antibacterial agent is selected from any one of alcohol antibacterial agents, silver antibacterial agents, imidazole antibacterial agents, copper antibacterial agents, zinc antibacterial agents, aldehyde antibacterial agents, acylanilide antibacterial agents, thiazole antibacterial agents, ketone antibacterial agents, biguanide antibacterial agents, and phenolic antibacterial agents or a combination thereof.

[0070] In the preferred technical solution of the present invention, the antibacterial agent is selected from any one of phenoxyethanol (PHE-SP10), Germall IS45, and ZEOMIC AWION, or a combination thereof.

[0071] In a preferred technical solution of the present invention, the hydrophobic agent is selected from any one of an organosilicon hydrophobic agent, paraffin, a fluorocarbon polymer hydrophobic agent, and a fatty acid soap, or a combination thereof.

[0072] In a preferred technical solution of the present invention, the hydrophobic agent is selected from any one of Wacker BS4004, TEGO Phobe 1500N, paraffin, or a combination thereof.

[0073] In the preferred technical solution of the present invention, the composition contains 0.05-1% of the colorant by weight.

[0074] In the preferred technical solution of the present invention, the colorant is selected from any one or a combination of iron oxide colorants, titanium oxide colorants, phthalocyanine colorants, azo colorants, and methylcalcein complexes, and is preferably selected from any one or a combination of titanium dioxide, phthalocyanine blue, and iron oxide red.

[0075] In the preferred technical solution of the present invention, the composition contains 0.05-1% of the initiator by weight.

[0076] In a preferred technical solution of the present invention, the initiator is selected from any one of an azo initiator and a peroxide initiator or a combination thereof.

[0077] In the preferred technical solution of the present invention, the composition contains 0.05-1% of the coupling agent by weight.

[0078] In a preferred technical solution of the present invention, the coupling agent is selected from any one of a silane coupling agent, a titanate coupling agent, and an aluminate compound, or a combination thereof.

[0079] In a preferred technical solution of the present invention, the artificial stone composition does not contain cobalt element.

[0080] In the preferred technical solution of the present invention, the composition contains, by weight percentage, 80-90% aluminosilicate, 8-15% resin, 0.1-5% stabilizer, 0.05-1% colorant, 0.05-1% initiator and 0.05-1% coupling agent.

[0081] In the preferred technical solution of the present invention, the composition contains, by weight percentage, 40-65% of aluminum silicate, 25-45% of sodium magnesium silicate, 8-15% of resin, 0.1-1% of stabilizer, 0.05-1% of colorant, 0.05-1% of initiator and 0.05-1% of coupling agent.

[0082] In the preferred technical solution of the present invention, the composition contains 87.38% aluminosilicate, ORCHEM TM 727 unsaturated polyester resin 11.64%, titanium dioxide 0.29%, silane coupling agent (KH-570) 0.1%, azobisisobutyronitrile 0.1%, Germall IS45 0.1%, TEGO Phobe 1500N 0.1% and nano-alumina 0.29%.

[0083] In the preferred technical scheme of the present invention, the composition contains, by weight percentage, 60.52% of aluminum silicate, 27.93% of sodium magnesium silicate, 10.24% of SIL93BE-956 resin, 0.09% of phthalocyanine blue, 0.09% of silane coupling agent (KH-570), 0.09% of azobisisobutyronitrile, 0.1% of ZEOMIC AW10N, 0.2% of paraffin and 0.74% of glass fiber.

[0084] In the preferred technical solution of the present invention, the composition contains, by weight percentage, 46.17% aluminum silicate, 41.55% sodium magnesium silicate, 11.08% Brayton polyester resin, 0.09 parts of red iron oxide, 0.09% silane coupling agent (KH-570), 0.09% azobisisobutyronitrile, 0.09% PHE-SP10, 0.1% Wacker BS4004, and 0.74% carbon fiber.

[0085] In a preferred technical solution of the present invention, the UV resistance test of the artificial stone composition is above level 5, preferably above level 6.

[0086] In a preferred technical solution of the present invention, the artificial stone composition does not turn yellow when placed outdoors for more than 2 years, preferably for more than 5 years.

[0087] In a preferred technical solution of the present invention, the artificial stone composition does not crack when placed outdoors for more than 2 years, preferably for more than 5 years.

[0088] Another object of the present invention is to provide a use of the artificial stone composition of the present invention in preparing building materials that can be used indoors and outdoors.

[0089] In a preferred technical solution of the present invention, the building material is selected from any one of a countertop, a floor, a furniture surface, a building decorative panel, and a wall tile.

[0090] Unless otherwise specified, the present invention adopts the following methods to test the properties of the artificial stone composition and its products.

[0091] 1. XRD detection: using JY / T 009-1996 detection.

[0092] 2. UV resistance: tested using ASTM D4329-13.

[0093] 3. Antibacterial test: tested using ASTM E2180-18.

[0094] 4. Glass transition temperature of the resin: detected by differential scanning calorimetry (DSC).

[0095] 5. Crack resistance test: Boil the board to be tested in 100℃ boiling water for 30 minutes, take it out of the boiling water, and freeze it at -20℃ for 30 minutes to observe the cracks of the board. If no cracks are observed on the board to be tested, repeat the boiling and freezing operations as described above until cracks are observed on the board to be tested.

[0096] 6. Surface water drip test: Dip chopsticks in water and drop it on the board, and observe the changes of the water drops on the board.

[0097] Unless otherwise specified, when the present invention relates to the percentage between liquids, the percentage is volume / volume percentage; when the present invention relates to the percentage between liquids and solids, the percentage is volume / weight percentage; when the present invention relates to the percentage between solids and liquids, the percentage is weight / volume percentage; the rest are weight / weight percentages.

[0098] Compared with the prior art, the beneficial effects of the present invention include:

[0099] 1. The artificial stone composition of the present invention scientifically selects components and proportions, and adds a stabilizer composed of antibacterial materials, hydrophobic materials, nanomaterials or fiber materials in a certain mass ratio, which significantly improves and enhances the mechanical properties of the composition, has good resistance to temperature difference destructiveness, water cracking resistance, weather resistance and bacteria resistance, effectively avoids the generation of aging waste, significantly reduces material costs and construction costs of replacing materials, and has the advantages of greening and environmental protection.

[0100] 2. The method for preparing the artificial stone composition of the present invention is easy to operate, reduces construction difficulty, saves production time, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0101] Figure 1 XRD spectrum of the artificial stone plate of Example 1. DETAILED DESCRIPTION

[0102] The details of the present invention are further explained and described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0103] Example 1 Preparation of artificial stone plate of the present invention

[0104] Composition of artificial stone slabs:

[0105]

[0106]

[0107] The preparation of artificial stone slabs includes the following steps:

[0108] (1) Weigh the required amount of titanium dioxide, silane coupling agent (KH-570), azobisisobutylnitrile, Germall IS45, TEGO Phobe 1500N and nano-alumina and add them to the required amount of ORCHEM TM 727 unsaturated polyester resin, stirring (200r / min) until mixed evenly, and then adding 100-1000 mesh aluminosilicate filler and 6-100 mesh aluminosilicate filler in sequence under stirring (200r / min) until mixed evenly to obtain a mixture;

[0109] (2) passing the mixture obtained in step (1) through a vacuum high-frequency vibration plate and vibrating and compressing it for 10 minutes under a vacuum degree of -0.1 MPa to obtain a compressed product;

[0110] (3) The compressed product obtained in step (2) is sent to a curing furnace and heated and cured at 100° C. for 40 minutes to obtain the product.

[0111] The XRD pattern of the artificial stone plate prepared in Example 1 is as follows: Figure 1 , crystalline silicon dioxide (SiO2) was not detected and cobalt was not contained. The artificial stone plate prepared in Example 1 was tested by the method of the present invention, and the UV resistance level was 6, the crack resistance level was no cracks after 1000 cycles, the antibacterial rate was 72%, and the surface water drop test result was water droplets.

[0112] Embodiment 2: The method for preparing the artificial stone plate of the present invention

[0113] Composition of artificial stone slabs:

[0114]

[0115] The preparation of artificial stone slabs includes the following steps:

[0116] (1) Weigh the required amount of phthalocyanine blue, silane coupling agent (KH-570), azobisisobutylnitrile, ZEOMIC AW10N, paraffin wax and glass fiber, add them to the required amount of SIL93BE-956 resin, stir (200 r / min) until the mixture is uniformly mixed, and then add 100-1000 mesh aluminum silicate filler and 6-100 mesh sodium magnesium silicate filler in sequence under stirring (200 r / min) until the mixture is uniformly mixed to obtain a mixture;

[0117] (2) passing the mixture obtained in step (1) through a vacuum high-frequency vibration plate and vibrating and compressing it for 10 minutes under a vacuum degree of -0.1 MPa to obtain a compressed product;

[0118] (3) The compressed product obtained in step (2) is sent to a curing furnace and heated and cured at 120° C. for 30 min.

[0119] The artificial stone plate prepared in Example 2 was tested by the method of the present invention. The UV resistance level was 6, the crack resistance level was no cracks after 1000 cycles, the antibacterial rate was 78%, and the surface water drop test result was water droplets.

[0120] Example 3: Preparation of artificial stone board of the present invention

[0121] Composition of artificial stone slabs:

[0122]

[0123] The preparation of artificial stone slabs includes the following steps:

[0124] (1) Weighing required amounts of red iron oxide, silane coupling agent (KH-570), azobisisobutylnitrile, PHE-SP10, Wacker BS4004 and carbon fiber, adding to required amount of Brayton polyester resin, stirring (200 r / min) until mixed uniformly, and then adding 100-1000 mesh aluminum silicate filler and 6-100 mesh sodium magnesium silicate filler in sequence under stirring (200 r / min) until mixed uniformly to prepare a mixture;

[0125] (2) passing the mixture obtained in step (1) through a vacuum high-frequency vibration plate and vibrating and compressing it for 10 minutes under a vacuum degree of -0.1 MPa to obtain a compressed product;

[0126] (3) The compressed product obtained in step (2) is sent to a curing furnace and heated and cured at 150° C. for 30 minutes to obtain the product.

[0127] The artificial stone plate prepared in Example 3 was tested by the method of the present invention. The UV resistance level was 6, the crack resistance level was no cracks after 1000 cycles, the antibacterial rate was 80%, and the surface water drip test result was water droplets.

[0128] Example 4: Preparation of artificial stone board of the present invention

[0129] Composition of artificial stone slabs:

[0130]

[0131]

[0132] The preparation of artificial stone slabs includes the following steps:

[0133] (1) Weighing required amounts of red iron oxide, silane coupling agent (KH-570), azobisisobutylnitrile, PHE-SP10, Wacker BS4004 and carbon fiber, adding to required amount of Brayton polyester resin, stirring (200 r / min) until mixed uniformly, and then adding 100-1000 mesh aluminum silicate filler and 6-100 mesh sodium magnesium silicate filler in sequence under stirring (200 r / min) until mixed uniformly to prepare a mixture;

[0134] (2) passing the mixture obtained in step (1) through a vacuum high-frequency vibration plate and vibrating and compressing it for 10 minutes under a vacuum degree of -0.1 MPa to obtain a compressed product;

[0135] (3) The compressed product obtained in step (2) is sent to a curing furnace and heated and cured at 150° C. for 30 minutes to obtain the product.

[0136] The artificial stone plate prepared in Example 4 was tested by the method of the present invention. The UV resistance level was 6, the crack resistance level was no cracks after 1000 cycles, the antibacterial rate was 76%, and the surface water drop test result was water droplets.

[0137] Comparative Example 1

[0138] The formula of the artificial stone composition is:

[0139]

[0140]

[0141] The preparation method of the plate is:

[0142] (1) The silicate is crushed to an average particle size of less than 100 mesh, and then added into a non-gravity mixer with a coupling agent, an initiator, and a colorant in proportion, and stirred and mixed at a speed of 200 r / min for 3 minutes, and then the resin is added and stirred and mixed for another 3 minutes to make the mixture of these dry ingredients uniform;

[0143] (2) passing the uniform mixture obtained in step (1) through a vacuum high-frequency vibration plate, and vibrating and compressing it under a vacuum of about -0.1 MPa for 10 minutes to obtain a compressed product;

[0144] (3) The compressed product obtained in step (2) is sent to a curing furnace and heated at 100° C. for 40 minutes to be cured.

[0145] The method of the present invention was used to test the artificial stone board prepared in Comparative Example 1. The UV resistance level was 4, the crack resistance was such that cracks appeared after 10 cycles, the antibacterial rate was 8.3%, and the surface drip test result was that water spread on the board surface.

[0146] Test Example 1Investigation on the stability of the artificial stone plate of the present invention

[0147] The artificial stone slabs prepared in Examples 1-4 were placed outdoors, and their color changes and cracks were observed and recorded every day. The colors were normal and there were no cracks within 5 years.

[0148] The above description of the specific embodiments of the present invention does not limit the present invention. Those skilled in the art may make various changes or modifications based on the present invention. As long as they do not depart from the spirit of the present invention, they should all fall within the scope of protection of the claims of the present invention.

Claims

1. An artificial stone composition, which contains, by weight percentage, 80-95% silicate filler, 4-15% resin, 0.1-5% stabilizer, 0.05-5% colorant, 0.05-5% initiator and 0.05-5% coupling agent, wherein: The silicate is selected from any one of aluminum silicate and sodium magnesium silicate or a combination thereof, the particle size of the silicate filler is 6 mesh to 1000 mesh, the glass transition temperature of the resin is not less than 80°C, The stabilizer is composed of an antibacterial agent: a hydrophobic agent: a nanomaterial or a fiber material in a mass ratio of 1:1-2:5-10; The resin is a polyester resin; The nanomaterial is a nano oxide; The fiber material is selected from any one of carbon fiber and glass fiber or a combination thereof; The antibacterial agent is selected from any one of alcohol antibacterial agents, silver antibacterial agents, imidazole antibacterial agents or a combination thereof; The hydrophobic agent is selected from any one of silicone hydrophobic agents and paraffin wax or a combination thereof; The quartz sand contained in the composition is ≤ 4%; The aluminum element: silicon element: oxygen element in the aluminosilicate is composed in a mass ratio of 1:1-10:1-10; The sodium magnesium silicate is composed of magnesium element: sodium element: silicon element: oxygen element in a mass ratio of 1:1-10:10-20:20-30.

2. The composition as claimed in claim 1, wherein the aluminum element: silicon element: oxygen element in the aluminosilicate is composed in a mass ratio of 1: (1.5-5): (3-8).

3. The composition according to claim 1, wherein the mass ratio of magnesium element: sodium element: silicon element: oxygen element in the sodium magnesium silicate is 1: (5-8): (10-15): (25-30).

4. The composition according to claim 1, wherein the glass transition temperature of the resin is not less than 100°C.

5. The composition of claim 1, wherein the mass ratio of the aluminum silicate in the composition to the sodium magnesium silicate is 1-5:1 in weight percentage.

6. The composition of claim 5, wherein the mass ratio of the aluminum silicate to the sodium magnesium silicate in the composition is 1-3:1 by weight percentage.

7. The composition as claimed in claim 1, wherein the quartz sand contained in the composition is ≤3% by weight.

8. The composition as claimed in claim 7, wherein the quartz sand contained in the composition is ≤2% by weight.

9. The composition as claimed in claim 8, wherein the quartz sand contained in the composition is ≤ 1% by weight.

10. The composition according to claim 9, wherein the composition substantially does not contain quartz sand, wherein the substantially does not contain quartz sand means that quartz sand is not detected in the composition or the quartz sand contained in the composition is zero.

11. The composition according to any one of claims 1 to 10, wherein the composition contains 10 to 15% of resin by weight.

12. The composition according to any one of claims 1 to 10, wherein the resin is any one of ORCHEM™ 727 unsaturated polyester resin, SIL93BE-956 resin, and Brayton polyester resin, or a combination thereof.

13. The composition according to any one of claims 1 to 10, wherein the composition contains 0.3-3% of a stabilizer by weight.

14. The composition according to any one of claims 1 to 10, wherein the particle size of the nanomaterial is not higher than 500 nm.

15. The composition according to any one of claims 1 to 10, wherein the length of the fiber material is not less than 3 mm.

16. The composition according to any one of claims 1 to 10, wherein the antibacterial agent is selected from any one of phenoxyethanol (PHE-SP10), Germall IS45, ZEOMIC AWION or a combination thereof.

17. The composition according to any one of claims 1 to 10, wherein the hydrophobic agent is selected from any one of Wacker BS4004, TEGO Phobe 1500N, paraffin wax, or a combination thereof.

18. The composition according to any one of claims 1 to 10, wherein the composition contains 0.05-1% of a colorant by weight.

19. The composition according to any one of claims 1 to 10, wherein the colorant is selected from any one of iron oxide colorants, titanium oxide colorants, phthalocyanine colorants, azo colorants, and methylcalcein complexes, or a combination thereof.

20. The composition according to claim 19, wherein the colorant is selected from any one of titanium dioxide, phthalocyanine blue, and red iron oxide, or a combination thereof.

21. The composition according to any one of claims 1 to 10, wherein the composition contains 0.05-1% of an initiator by weight.

22. The composition according to any one of claims 1 to 10, wherein the initiator is selected from any one of an azo initiator and a peroxide initiator or a combination thereof.

23. The composition according to any one of claims 1 to 10, wherein the composition contains 0.05-1% coupling agent by weight.

24. The composition according to any one of claims 1 to 10, wherein the coupling agent is selected from any one of a silane coupling agent, a titanate coupling agent, and an aluminate compound, or a combination thereof.

25. The composition according to any one of claims 1 to 10, wherein the artificial stone composition does not contain cobalt.

26. A composition as claimed in any one of claims 1 to 11, comprising, by weight percentage, 80-90% aluminosilicate, 8-15% resin, 0.1-5% stabilizer, 0.05-1% colourant, 0.05-1% initiator and 0.05-1% coupling agent.

27. as any described composition of claim 1-10, in weight percentage, contain aluminosilicate 40-65%, sodium magnesium silicate 25-45%, resin 8-15%, stabilizer 0.1-5%, colorant 0.05-1%, initiator 0.05-1% and coupling agent 0.05-1% in the composition.

28. The composition of claim 27, wherein the composition comprises, by weight percentage, 87.38% aluminosilicate, 11.64% ORCHEM™ 727 unsaturated polyester resin, 0.29% titanium dioxide, 0.1% silane coupling agent (KH-570), 0.1% azobisisobutyronitrile, 0.1% Germall IS45, 0.1% TEGO Phobe 1500N and 0.29% nano-alumina.

29. The composition of claim 27, wherein the composition comprises, by weight percentage, 60.52% aluminosilicate, 27.93% sodium magnesium silicate, 10.24% SIL93BE-956 resin, 0.09% phthalocyanine blue, 0.09% silane coupling agent (KH-570), 0.09% azobisisobutyronitrile, 0.1% ZEOMIC AW10N, 0.2% paraffin wax, and 0.74% glass fiber.

30. The composition of claim 27, wherein the composition comprises, by weight percentage, 46.17% aluminosilicate, 41.55% sodium magnesium silicate, 11.08% Brayton polyester resin, 0.09 part of red iron oxide, 0.09% of silane coupling agent (KH-570), 0.09% of azobisisobutyronitrile, 0.09% of PHE-SP10, 0.1% of Wacker BS4004, and 0.74% of carbon fiber.

31. The composition according to any one of claims 1 to 10, wherein the UV resistance of the artificial stone composition is above level 5.

32. The composition according to claim 31, wherein the UV resistance of the artificial stone composition is above level 6.

33. The composition according to any one of claims 1 to 10, wherein the artificial stone composition does not turn yellow when placed outdoors for more than 2 years.

34. The composition as claimed in claim 33, wherein the artificial stone composition does not turn yellow when placed outdoors for more than 5 years.

35. The composition according to any one of claims 1 to 10, wherein the artificial stone composition does not crack when placed outdoors for more than 2 years.

36. The composition as claimed in claim 35, wherein the artificial stone composition does not crack when placed outdoors for more than 5 years.

37. The composition according to any one of claims 1 to 10, wherein the preparation of the artificial stone composition comprises the following steps: (1) Weigh the required amount of stabilizer, colorant, coupling agent, and initiator, add them to the required amount of resin, stir until the mixture is uniform, and then add 100-1000 mesh silicate filler and 6-100 mesh silicate filler in sequence under stirring to prepare a mixture; (2) Under a vacuum degree of -0.1 MPa, the obtained mixture is vacuum compressed to obtain a sheet precursor; (3) The prepared board precursor is heated and solidified to obtain a board product.

38. The composition as claimed in claim 37, wherein the stirring condition in step (1) is 100-300 r / min*1-30 min.

39. The composition as claimed in claim 38, wherein the stirring condition in step (1) is 150-250 r / min*5-25 min.

40. The composition as claimed in claim 37, wherein the compression in step (2) is vibration compression for 1 to 60 minutes.

41. The composition of claim 37, wherein the curing conditions in step (3) are 70°C-150°C*10-300min.

42. The composition of claim 41, wherein the curing conditions in step (3) are 85°C-110°C*20-200min.

43. The composition of claim 42, wherein the curing conditions in step (3) are 90-100°C*30-100min.

44. The method for preparing the artificial stone composition according to any one of claims 1 to 43, wherein the preparation of the artificial stone composition comprises the following steps: (1) Weigh the required amount of stabilizer, colorant, coupling agent, and initiator, add them to the required amount of resin, stir until the mixture is uniform, and then add 100-1000 mesh silicate filler and 6-100 mesh silicate filler in sequence under stirring to prepare a mixture; (2) Under a vacuum degree of -0.1 MPa, the obtained mixture is vacuum compressed to obtain a sheet precursor; (3) The prepared board precursor is heated and solidified to obtain a board product.

45. The method according to claim 44, wherein the stirring condition in step (1) is 100-300 r / min*1-30min.

46. ​​The method according to claim 45, wherein the stirring condition in step (1) is 150-250 r / min*5-25 min.

47. The method of claim 44, wherein the compression in step (2) is vibration compression for 1-60 minutes.

48. The method according to claim 44, wherein the curing conditions in step (3) are 70°C-150°C*10-300min.

49. The method according to claim 48, wherein the curing conditions in step (3) are 85°C-110°C*20-200min.

50. The method according to claim 49, wherein the curing conditions in step (3) are 90-100°C*30-100min.

51. Use of the artificial stone composition according to any one of claims 1 to 43 or the artificial stone composition prepared by the method according to any one of claims 44 to 50 in preparing building materials that can be used indoors or outdoors.

52. The use according to claim 51, wherein the building material is selected from any one of a countertop, a floor, a furniture surface, a building decorative panel, and a wall tile.

Citation Information

Patent Citations

  • Super-strength and anti-wear artificial quartz stone plate and production method thereof

    CN105948568A

  • Artificial quartz rock containing ceramic fragments and preparation method thereof

    CN107344823A